2015
DOI: 10.1038/srep17373
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of a Microbial Fuel Cell—A detailed study

Abstract: In contemporary society we observe an everlasting permeation of electron devices, smartphones, portable computing tools. The tiniest living organisms on Earth could become the key to address this challenge: energy generation by bacterial processes from renewable stocks/waste through devices such as microbial fuel cells (MFCs). However, the application of this solution was limited by a moderately low efficiency. We explored the limits, if any, of additive manufacturing (AM) technology to fabricate a fully AM-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Today, there are many 3D printers commercially available allowing the processing of materials such as polymers, ceramics, metals, tissues, wax, etc. at different scales . However, although a lot of development has been done in 3D printing, it is still difficult to combine different materials in a single 3D object using a single 3D manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there are many 3D printers commercially available allowing the processing of materials such as polymers, ceramics, metals, tissues, wax, etc. at different scales . However, although a lot of development has been done in 3D printing, it is still difficult to combine different materials in a single 3D object using a single 3D manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Additive Manufacturing (AM) is an emerging technology that builds three dimensional objects from computer-aided design (CAD) models by adding layer-by-layer of material13. It has attracted tremendous attention from both the research1415 and industrial communities. The prevailing industrial applications are due to the advantages over conventional subtractive manufacturing processes such as: minimum materials waste (if any) and energy usage, less process time, no additional tooling costs, no size and shape limitations.…”
mentioning
confidence: 99%
“…Calignano et al. employed SLM to fabricate a bio‐inspired lattice aluminum alloy anode, which results in higher power densities compared with other metallic anodes . The results showed that the SLS constructed anode has low density, high surface area, and ideal surface roughness of a 3D microporous structure.…”
Section: Fuel Cell Advances Enabled By Am Technologiesmentioning
confidence: 99%